Aplikasi Pembelajaran Edukatif Bahasa Isyarat pada Sekolah Luar Biasa (SLB ) "Tunas Bangsa", Kota Balikpapan - Hidayati, Qory; Retno sari, Danar; Jamal, Nurwahidah; Manjelang, Sony Fajar (Journal of Applied Community Engagement, 2022)
One of the problems faced by Special Schools (SLB) in the city of Balikpapan is the very small number of special schools that handle deaf students and the very limited number of special teachers to train communication for students with special needs for the deaf. With the imbalance in the ratio of teachers and students, where the number of teachers is very small compared to the number of students with special needs for hearing impairment, many students cannot be handled regularly and sustainably in learning and practicing communicating using the Indonesian language. In addition to this, communication training activities take a long time and are continuous, so many teachers and students are bored and bored in these activities. Higher Education (PT) is one of the institutions that is expected to play an active role in the process of implementing knowledge transfer or knowledge transfer to the wider community in the form of dissemination of research results that have been carried out. Independent learning communication training for deaf students using the speech-impaired application system, aims to overcome the problem of the limited number of special schools and teachers who handle deaf students, overcome boredom and boredom in the teaching and learning process and accelerate communication skills for these students. Applications as a communication tool and there are educational games. Students can learn to communicate by imitating mouth movements (lips, teeth and tongue) to practice speaking according to the inputted text. This activity was held on July 15-16, 2022 at SLB Tunas Bangsa Balikpapan.